PENGGUNAAN DOKSISIKLIN HYCLATE SEBAGAI INHIBITOR MATRIKS METALLOPROTEINASE PADA TERAPI TAMBAHAN PERIODONTITIS - Risma Aprinda Kristanti (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2012)
Terbit.com Daily has reported that the prevalence of periodontitis increases related with age person. Found that 35,7% of patients with periodontitis in the group 30-39 years old to 66,5% in the group 50-59 years old, increase 89,2% in the group 80-90 years old. Periodontitis that commonly found is a chronic periodontitis which is occurs in individuals older than 45 years, but can also be found in children. The main characteristic of periodontitis is the damage of the periodontal connective tissue, alveolar bone, and the movement of the junctional epithelium to the apical. Bacterial components may directly or indirectly cause tissue damage. Inflammatory mediators product such as proteinases, cytokines, and prostaglandins are part of the host response that can also cause tissue damage. Matrix metalloproteinase (MMP) is a proteinase that can cause periodontal tissue damage by disrupting the extracellular matrix molecules in periodontal tissues. Since is known that MMP has a role in various pathological processes, therapy to inhibit activity MMP in pathological processes has developed. MMP inhibitors will be a useful adjunct therapy for the treatment of periodontal disease. Many products have been introduced as an MMP inhibitor, for example: tetracycline and various derivatives, such as doxycycline and minocycline which are capable of inhibiting the activity of several classes of MMPs. Doxycycline has the ability to inhibit the increase in collagenase activity that is pathological in subgingival and prevent periodontitis to become more severe.